Migration between Platforms - Gary Biglaiser; Jacques Crémer; André Veiga (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study incumbency advantage in markets with positive consumption externalities. Users of an incumbent platform receive stochastic opportunities to migrate to an entrant. They can accept a migration opportunity or wait for a future opportunity. In some circumstances, users have incentives to delay migration until others have migrated. If they all do so, no migration takes place, even when migration would have been Pareto-superior. This provides an endogenous micro-foundation for incumbency advantage. We use our framework to identify environments where incumbency advantage is larger.
Keywords: D85; L14; R23; L15; L16; 330; platform migration; standardization and compatibility; industry dynamics